Software-Defined Network for Internet of Things - Francisco Luís Araújo Fraga (2019)
It is clear that the growth on global Internet traffic must be somehow compensated with faster, simpler, scalable and more flexible solutions. With that in mind, it is important to understand how easily SDN can simplify this problem when compared to traditional networks. SDN is an in growing and potential topic designed to increase efficiency, flexibility and accelerate the introduction of new services with the support of scalability, representing the perfect way of performing resource management and intelligent service orchestration. Having in mind the huge amount of connected devices and its technology and characteristics evolution, it is inevitable to notice that a considerable continuous growth in the Internet generated traffic is happening. In light of this, the security threatening and direction of data network flow should be considered as crucial points to debate. The researching world should be aware that it is mandatory to guarantee a good behaviour on IoT downside characteristics (movement,safety, programmability and information management) and it is there when SDN turns out to be profitable. Because of the SDN separation between both planes (data and control), these technologies coupling can prove to be a turning point to the IoT world itself and the consideration and analysis of potential solutions should be taken into account. Due to the constant IoT evolving, more use cases are being considered as it provides a more solid behaviour when dealing with them. Since emerging technologies and NGN care about efficiency, they demand for the researchers to find solutions regarding the resources each individual situation requires. This Master Thesis project will focus on solving multiple use cases slices management problems, created on a SDN coupling with IoT framework. Because each considered slice deals with a specific use case and each one of them has different characteristics, distinct amounts of resources will be needed in order to provide the solution required QoS level.